WORKSHOP DAN PELATIHAN KEWIRAUSAHAAN MAHASISWA PRODI ADMINISTRASI BISNIS - Sigalingging, Andy Sahat Maasi; Leiwakabessy, Dominggus Rudolf; Hasim, Djamil; Sutrimono, Sutrimono (Jurnal Abdimas Bina Bangsa, 2024)
Entrepreneurship has become a primary focus in higher education, especially in the field of Business Administration, to support students in developing an entrepreneurial mindset and potential to become entrepreneurs. This dedication discusses the importance of entrepreneurship workshops and training for Business Administration students in preparing themselves to face the dynamic challenges of the business world. A qualitative method with a literature study approach is employed to investigate various relevant literature sources on this topic, including theories and practices of entrepreneurship in the context of higher education. Findings indicate that entrepreneurship workshops and training are effective in enhancing students' entrepreneurial competencies, such as creative thinking skills, decision-making, and risk management. Moreover, these training programs also contribute to increasing students' motivation and interest in starting their own businesses in the future. The results of this dedication can serve as a reference for educational institutions to develop more effective entrepreneurship workshop and training programs to support students' development into entrepreneurs.